ANALISIS KINERJA RANTAI PASOK (SUPPLY CHAIN) KOPI ROBUSTA DI KECAMATAN ULUBELU, KABUPATEN TANGGAMUS - Ade Sita Noviana; Agus Setiadi; Kustopo Budiraharjo (Universitas Galuh, 2022)
Coffee was a commodity that had good prospects for commerce. The high demand for coffee must be accompanied by a good supply chain in order for the trade to run effectively. The study aims to know the flow of products, information streams, and financial streams, as well as the performance of robusta coffee supply chain in Ulubelu district of Tanggamus regency. This site has been purposely chosen (purpossive) on the basis of ulubelu district's main producer of robusta coffee in the Tanggamus regency. The type of data collected is the primary data obtained through the methods of interviews and secondary data obtained from relevant libraries or literature. In addition, PT Ulubelu Cofco Abadi, the director for production and acquisition of goods, the Karya Taruna Gapoktan, and the research institute. Data is analyzed using a descriptive analysis to describe the flow of products, financial streams, and information streams. Supply Chain Operation Reference (SCOR) is used to account for the performance of the perpetual supply chain in PT Ulubelu Cofco Abadi that was agroindustry of robusta coffee. Research shows that three streams in robusta coffee supply chain in Ulubelu district of Tanggamus regency has not been optimal. The flow of information that goes on in the supply chain regarding daily price changes. The flow of products flows from farmers to middlemen, gatherers, traders, exporters/powdered coffee industry in the form of ose or green bean. A cash flow between marketing agencies flows from downstream to upstream and smoothly. The results of the robusta coffee supply chain performance in PT Ulubelu Cofco Abadi immortality were 82.31% of those included in the good classes.